The Determinants of Pass-Through of Market Conditions to Bank Retail Interest Rates in Belgium - Ferre De Graeve; Olivier De Jonghe; Rudi Vander Vennet (National Bank of Belgium, 2004)
We analyse the pass-through of money market rates to retail interest rates at the disaggregate level in the Belgian banking market. First, we measure the extent of pass-through for a total of fourteen products. We find that the response varies over loans and deposits and depends positively on the maturity of the product. Second, the launch of EMU has generally not resulted in more competitive pricing by banks. Third, we assess the importance of several biases and find that heterogeneity in price-setting behaviour should be accounted for in analysing the pass-through. Fourth, we analyse bank-specific determinants of heterogeneous interest rate pass-through. We find a role for capital, liquidity and market share and we relate these results to the various channels in monetary policy transmission and to the structure-conduct-performance hypothesis in banking.
Keywords: C23; E43; E52; G21; L11; 330; pass-through; Heterogeneous panel; aggregation bias; panel cointegration; retailbanking; bank-level interest rates; bank-level determinants; Geldpolitik; Geldpolitische Transmission; Zinsstruktur; Kredit; Belgien